2019
DOI: 10.1051/0004-6361/201834798
|View full text |Cite
|
Sign up to set email alerts
|

3D thermal modeling of two selected regions on comet 67P and comparison with Rosetta/MIRO measurements

Abstract: Context. The Microwave Instrument for the Rosetta Orbiter (MIRO) was one of the key instruments of the Rosetta mission, which acquired a wealth of data, in particular as the orbiter moved in the close environment of comet 67P/Churyumov-Gerasimenko (August 2014–September 2016). It was the only instrument of the Rosetta payload that was able to measure temperatures in the near-subsurface layers of the cometary nucleus down to a depth of some centimeters. This range is most relevant for understanding the mechanis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…For instance, Keller et al (2015) showed that self-heating could reach 50% of the total energy received in some areas of the neck region. Macher et al (2019) also showed that, even though the average contribution of self-heating in the regions they studied was evaluated to be 1% of the direct insolation, it can be enhanced in rough areas not reached by direct insolation. In these locations, it could reach as much as 50% of the direct insolation contribution.…”
Section: Local and Global Shape Effectsmentioning
confidence: 89%
See 1 more Smart Citation
“…For instance, Keller et al (2015) showed that self-heating could reach 50% of the total energy received in some areas of the neck region. Macher et al (2019) also showed that, even though the average contribution of self-heating in the regions they studied was evaluated to be 1% of the direct insolation, it can be enhanced in rough areas not reached by direct insolation. In these locations, it could reach as much as 50% of the direct insolation contribution.…”
Section: Local and Global Shape Effectsmentioning
confidence: 89%
“…Each facet gets its own boundary condition at the surface. Therefore, a 1D thermal evolution model is the best option, further justified by the results of Macher et al (2019), who found that temperature differences at the surface of 67P between a 1D and a 3D thermal simulation (i.e., accounting for lateral heat fluxes) amount to only ∼ 0.1%.…”
Section: Main Equationsmentioning
confidence: 97%
“…Third, the slow migration rate of scarp "h" may also point to stratigraphic differences in the volume of ice within the local subsurface. Specifically, scarps "d" and "a" may only be removing an entire seasonally processed layer of material (Figure 10), the thickness (L seasonal ) of which is simply the thermal skin depth, given by Macher et al (2019),…”
Section: Hypothesis and Interpretationsmentioning
confidence: 99%
“…We are particularly interested in the flat areas as this allows to use the least complex thermophysical model. Indeed, it was shown that surface roughness and the presence of shadows or cliffs, as well as self-heating effects need to be taken into account in non-flat regions (Macher et al 2019). By choosing particularly flat areas, we avoid these effects and increase the reliability of our results.…”
Section: Selection Of a Suitable Miro Data Setmentioning
confidence: 90%
“…In this work, we use the MIRO observations to derive the submm/mm optical properties of the near-surface material of comet 67P. In contrast to Schloerb et al (2015) and Macher et al (2019), who assumed an absorption coefficient for their calculations, we use a thermophysical model, which provides a temperature profile for the upper layers of the cometary nucleus. We then derive the complex index of refraction by fitting the temperature measurements of 67P's sub-surface made by MIRO with synthetic temperatures derived from the thermophysical and radiative-transfer model.…”
Section: Introductionmentioning
confidence: 99%